Teacher efforts to prepare implementation of Kurikulum Merdeka in elementary school - Isti Qotimah; Rusman Rusman (Himpunan Pengembang Kurikulum Indonesia, 2024)
The Kurikulum Merdeka seeks to improve the quality of human resources according to community needs. This research aims to describe and analyze teacher readiness in implementing the Kurikulum Merdeka for elementary schools in Coblong District to determine the curriculum's implementation based on diverse school backgrounds. This research uses a quantitative approach through descriptive methods with instruments like questionnaires and documentation studies. The sample for this research was all elementary school teachers who implemented the Kurikulum Merdeka and were selected to run the Sekolah Penggerak program, totaling 45 teachers. The findings relate to teachers' emotional, cognitive, and behavioral readiness in implementing Kurikulum Merdeka. Most teachers are ready to implement Kurikulum Merdeka by participating in training and socializing with other teachers. Readiness is also demonstrated in designing, implementing, and assessing learning. Positive behavior towards curriculum implementation is realized through partnerships and time management efforts to achieve goals. Overall, in every aspect of teacher readiness, it shows that most Sekolah Penggerak elementary school teachers in Coblong District, Bandung City, are ready to implement Kurikulum Merdeka. Abstrak Kurikulum merdeka berupaya meningkatkan kualitas sumber daya manusia sesuai kebutuhan masyarakat. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis kesiapan guru dalam implementasi kurikulum merdeka sekolah dasar Kecamatan Coblong guna mengetahui implementasi kurikulum berdasarkan latar belakang sekolah yang beragam. Penelitian ini menggunakan pendekatan kuantitatif melalui metode deskriptif dengan instrumen berupa angket dan studi dokumentasi. Sampel penelitian ini adalah seluruh guru sekolah dasar yang menerapkan kurikulum merdeka dan terpilih untuk menjalankan program sekolah penggerak berjumlah 45 guru. Hasil temuan berkaitan dengan kesiapan emosi, kognitif dan perilaku guru dalam implementasi kurikulum merdeka. Sebagian besar guru siap mengimplementasikan kurikulum merdeka dengan mengikuti pelatihan maupun bersosialisasi kepada guru lainnya. Kesiapan juga ditunjukan dalam merancang, melaksanakan, dan menilai pembelajaran. Perilaku positif terhadap implementasi kurikulum terwujud melalui adanya kemitraan dan upaya manajemen waktu untuk mencapai tujuan. Secara keseluruhan, pada setiap aspek kesiapan guru menunjukkan bahwa sebagian besar guru sekolah dasar penggerak di Kecamatan Coblong Kota Bandung telah siap mengimplementasikan kurikulum merdeka. Kata Kunci: Pendidikan; kurikulum; kesiapan guru; sekolah dasar